PENGARUH TAMPILAN TOKO ( STORE ATMOSPHERE ) TERHADAP KEPUASAN KONSUMEN PADA UKM KULINER DI KELURAHAN DEPOK JAYA, KECAMATAN PANCORAN MAS, KOTA DEPOK. - faisal H Batubara; chairul hadi (Politeknik APP Jakarta, 2021)
The culinary business is compared to other businesses in the city of Depok during the pandemic, its development is ranked first, this is what makes the author interested in conducting research on